On the issue of psychodiagnosis of Internet addiction against the background of social isolation and security crisis - Stoliarenko, A. M.; Horodokin, A. D. (Modern medical technology, 2023)
Aim: to analyze the diagnostic informativeness of the Kimberly Young’s Internet Addiction Test in the conditions of social isolation and security crisis in Ukraine. Materials and methods. The study was conducted on a contingent of 120 respondents aged 18 to 23 students, who have an experience of permanent stay in conditions of social isolation in Ukraine during 2020–2023. The distribution of the contingent by gender was symmetrical. The research method is a structured psychological interview (according to the structure of Kimberly Young’s Internet Addiction Test; in addition to the quantified assessment, the respondent was given the opportunity to provide an open answer and a comment). Results. The analysis of the correctness of the test questions based on the open answers and comments of the respondents made it possible to establish a number of problems that violate the correctness of the assess- ment, namely: technical anachronisms – cases when the question is based on outdated technical facts that have changed radically since the time of formulation (mostly due to the appearance of mobile devices); social anachronisms – cases when the question is based on prejudice regarding violations of social functioning and social pressure on a person due to the use of the Internet by his social environment; introspection shift – cases when the questions are based on a prejudice about the negative evaluation of using the Internet; situational incorrectness – cases when the question loses its correctness in conditions of motivated social isolation and/or external danger; inaccuracies of translation and adaptation – cases when the translation of test questions into Ukrainian leads to inaccuracy or distortion of the meaning of the original question. Conclusions. 5 categories of problems with the correctness of Kimberly Young’s Internet Addiction Test have been identified. Each of the 20 questions of the test was analyzed on the basis of the respondents’ open answers and the comments provided by them. The existing problems of correctness related to the change in the technical paradigm of using the Internet were detected, as well as the socio-cultural changes that have occurred over the last 25 years, and with the situation of social isolation and security crisis, which significantly change the context of Internet use. This necessitates the revision and clarification of both the phenomenon of Internet addiction itself and the methodology of its diagnosis.